Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Let's solve each quadratic equation step by step to find the correct solution sets.
1. Equation: [tex]\(a^2 - 9a + 14 = 0\)[/tex]
To solve this, we can factorize the quadratic expression:
[tex]\[ a^2 - 9a + 14 = (a - 7)(a - 2) = 0 \][/tex]
Setting each factor to zero gives us:
[tex]\[ a - 7 = 0 \quad \text{or} \quad a - 2 = 0 \][/tex]
Thus, the solutions are:
[tex]\[ a = 7 \quad \text{and} \quad a = 2 \][/tex]
Solution set: [tex]\(\{7, 2\}\)[/tex]
2. Equation: [tex]\(a^2 + 9a + 14 = 0\)[/tex]
To solve this, we can factorize the quadratic expression:
[tex]\[ a^2 + 9a + 14 = (a + 7)(a + 2) = 0 \][/tex]
Setting each factor to zero gives us:
[tex]\[ a + 7 = 0 \quad \text{or} \quad a + 2 = 0 \][/tex]
Thus, the solutions are:
[tex]\[ a = -7 \quad \text{and} \quad a = -2 \][/tex]
Solution set: [tex]\(\{-7, -2\}\)[/tex]
3. Equation: [tex]\(a^2 + 3a - 10 = 0\)[/tex]
To solve this, we can factorize the quadratic expression:
[tex]\[ a^2 + 3a - 10 = (a + 5)(a - 2) = 0 \][/tex]
Setting each factor to zero gives us:
[tex]\[ a + 5 = 0 \quad \text{or} \quad a - 2 = 0 \][/tex]
Thus, the solutions are:
[tex]\[ a = -5 \quad \text{and} \quad a = 2 \][/tex]
Solution set: [tex]\(\{2, -5\}\)[/tex]
4. Equation: [tex]\(a^2 + 5a - 14 = 0\)[/tex]
To solve this, we can factorize the quadratic expression:
[tex]\[ a^2 + 5a - 14 = (a + 7)(a - 2) = 0 \][/tex]
Setting each factor to zero gives us:
[tex]\[ a + 7 = 0 \quad \text{or} \quad a - 2 = 0 \][/tex]
Thus, the solutions are:
[tex]\[ a = -4 \quad \text{and} \quad a = 2 \][/tex]
Solution set: [tex]\(\{2, -4\}\)[/tex]
5. Equation: [tex]\(a^2 - 5a - 14 = 0\)[/tex]
To solve this, we can factorize the quadratic expression:
[tex]\[ a^2 - 5a - 14 = (a - 7)(a + 2) = 0 \][/tex]
Setting each factor to zero gives us:
[tex]\[ a - 7 = 0 \quad \text{or} \quad a + 2 = 0 \][/tex]
Thus, the solutions are:
[tex]\[ a = 7 \quad \text{and} \quad a = -2 \][/tex]
Solution set: [tex]\(\{7, -2\}\)[/tex]
So, the correct matches are:
1. [tex]\(a^2 - 9a + 14 = 0 \quad \longrightarrow \quad \{7, 2\}\)[/tex]
2. [tex]\(a^2 + 9a + 14 = 0 \quad \longrightarrow \quad \{-7, -2\}\)[/tex]
3. [tex]\(a^2 + 3a - 10 = 0 \quad \longrightarrow \quad \{2, -5\}\)[/tex]
4. [tex]\(a^2 + 5a - 14 = 0 \quad \longrightarrow \quad \{2, -4\}\)[/tex]
5. [tex]\(a^2 - 5a - 14 = 0 \quad \longrightarrow \quad \{7, -2\}\)[/tex]
1. Equation: [tex]\(a^2 - 9a + 14 = 0\)[/tex]
To solve this, we can factorize the quadratic expression:
[tex]\[ a^2 - 9a + 14 = (a - 7)(a - 2) = 0 \][/tex]
Setting each factor to zero gives us:
[tex]\[ a - 7 = 0 \quad \text{or} \quad a - 2 = 0 \][/tex]
Thus, the solutions are:
[tex]\[ a = 7 \quad \text{and} \quad a = 2 \][/tex]
Solution set: [tex]\(\{7, 2\}\)[/tex]
2. Equation: [tex]\(a^2 + 9a + 14 = 0\)[/tex]
To solve this, we can factorize the quadratic expression:
[tex]\[ a^2 + 9a + 14 = (a + 7)(a + 2) = 0 \][/tex]
Setting each factor to zero gives us:
[tex]\[ a + 7 = 0 \quad \text{or} \quad a + 2 = 0 \][/tex]
Thus, the solutions are:
[tex]\[ a = -7 \quad \text{and} \quad a = -2 \][/tex]
Solution set: [tex]\(\{-7, -2\}\)[/tex]
3. Equation: [tex]\(a^2 + 3a - 10 = 0\)[/tex]
To solve this, we can factorize the quadratic expression:
[tex]\[ a^2 + 3a - 10 = (a + 5)(a - 2) = 0 \][/tex]
Setting each factor to zero gives us:
[tex]\[ a + 5 = 0 \quad \text{or} \quad a - 2 = 0 \][/tex]
Thus, the solutions are:
[tex]\[ a = -5 \quad \text{and} \quad a = 2 \][/tex]
Solution set: [tex]\(\{2, -5\}\)[/tex]
4. Equation: [tex]\(a^2 + 5a - 14 = 0\)[/tex]
To solve this, we can factorize the quadratic expression:
[tex]\[ a^2 + 5a - 14 = (a + 7)(a - 2) = 0 \][/tex]
Setting each factor to zero gives us:
[tex]\[ a + 7 = 0 \quad \text{or} \quad a - 2 = 0 \][/tex]
Thus, the solutions are:
[tex]\[ a = -4 \quad \text{and} \quad a = 2 \][/tex]
Solution set: [tex]\(\{2, -4\}\)[/tex]
5. Equation: [tex]\(a^2 - 5a - 14 = 0\)[/tex]
To solve this, we can factorize the quadratic expression:
[tex]\[ a^2 - 5a - 14 = (a - 7)(a + 2) = 0 \][/tex]
Setting each factor to zero gives us:
[tex]\[ a - 7 = 0 \quad \text{or} \quad a + 2 = 0 \][/tex]
Thus, the solutions are:
[tex]\[ a = 7 \quad \text{and} \quad a = -2 \][/tex]
Solution set: [tex]\(\{7, -2\}\)[/tex]
So, the correct matches are:
1. [tex]\(a^2 - 9a + 14 = 0 \quad \longrightarrow \quad \{7, 2\}\)[/tex]
2. [tex]\(a^2 + 9a + 14 = 0 \quad \longrightarrow \quad \{-7, -2\}\)[/tex]
3. [tex]\(a^2 + 3a - 10 = 0 \quad \longrightarrow \quad \{2, -5\}\)[/tex]
4. [tex]\(a^2 + 5a - 14 = 0 \quad \longrightarrow \quad \{2, -4\}\)[/tex]
5. [tex]\(a^2 - 5a - 14 = 0 \quad \longrightarrow \quad \{7, -2\}\)[/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.